The Influence of Teacher’s Motivation, Competency and Work Environment To The Effectiveness of Virtual Learning of The Junior High Schools In Rancamaya Bogor Year 2020 - Ariesta, Eliza; Djemahir, Arlina Arifin; Siahaan, Ronny Rudolf (CV. Ridwan Publisher, 2021)
This research aims to analyze the effect of teacher motivation, teacher competency, and teacher work environment on the effectiveness of virtual (distance) learning at some state-owned Junior High Schools located in marginal villages within the Bogor region in West Java Province as the densest population province in Indonesia. The research was conducted at 5 state-owned junior high schools located in marginal villages within the Bogor region in West Java Province, using a survey research method. Research respondents in five state-owned Junior High schools with a total of 100 teachers, selected based on cluster sampling technique (area sampling). The results showed that teacher motivation affects negatively and did not affect significantly the effectiveness of virtual learning, competency does not impact significantly the effectiveness of the virtual learning, and work environment does not significantly influence the effectiveness of virtual learning